The Semiotics Aspect In The Dayak Motif Design: A Visual Communication Study Of Sign System, The Signification, And Application Among The Dayak Ethnic Groups In Borneo - Kanyan, Ringah (2022)
This study investigates the semiotics aspect of the Dayak motifs in the visual communication system of the Dayak ethnics groups in Borneo. The aim is to examine the correlation between the theoretical and cultural meaning of the Dayak motif. The study will propose a conceptual model for interpreting and validating the semiological signification of the Dayak motif as a sign in visual communication. The significance of this study highlights the communicative role of Dayak motifs as the principal value in the creation of motifs overcoming the role of aesthetics as a complementary value in the visual presentation of a Dayak motif. This research employs a qualitative and a quantitative mixed-method approach to answer the research objectives. The qualitative research results were obtained by photographic observation and in-depth interview methods. The qualitative analysis aims to identify the authenticity of motif design characteristics and their original meaning. Four Dayak ethnic groups consisting of Iban, Apo Kayan or Orang Ulu, Ngaju, and Dayak Darat or Bidayuh, from four different geographical locations, were selected for analysis. The quantitative results were obtained by articulating the design elements and principles of the Dayak motif specimens collected from secondary data.